Expression of CD44v6 and lymphatic vessel density in early gastric cancer tissues and their clinical significance - Sun, Yuting (Pak J Med Sci, 2019)
OBJECTIVE: To explore the relationships between expression of CD44v6, lymphatic vessel density (LVD) and the clinicopathological parameters of patients. METHODS: One hundred early gastric cancer tissues, 55 high-grade gastric intraepithelial neoplasia (HGIN) tissues, 60 low-grade gastric intraepithelial neoplasia (LGIN) tissues and 60 chronic superficial gastritis tissues were collected and set as gastric cancer group, HGIN group, LGIN group and gastritis group respectively. The expression of CD44v6 and LVD of patients in all the groups were detected using two-step immunohistochemical method to analyze the relationships between the expression of CD44v6 and lymphatic vessel density in early gastric cancer tissues and their relationships with the clinicopathological parameters of patients. The values of LVD in predicting lymph node metastasis in early gastric cancer were evaluated using receiver operating characteristic (ROC) curve. RESULTS: The positive expression of CD44v6 and LVD in the gastritis group, LGIN group, HGIN group and gastric cancer group gradually increased. The positive expression of CD44v6 and LVD in early gastric cancer tissues were in no correlation with the gender, age, tumor site, maximum diameter, differentiation degree and invasion depth (P>0.05) and in a correlation with lymphatic metastasis and lymphatic vessel invasion (P<0.06). The positive expression of CD44v6 in the early gastric cancer tissues was in a positive correlation with LVD (P<0.05). The analysis of ROC curves suggested that the area under ROC curve of predicting lymphatic metastasis of early gastric cancer with LVD was 0.837 (95% CI: 0.756~0.910), and the cut-off value was 14; the corresponding sensitivity and specificity were 63.6% and 90.2 respectively. CONCLUSION: The expression of CD44v6 and LVD in early gastric cancer tissues are in a close correlation with the clinicopathologic features, and joint detection of expression of CD44v6 and LVD can be taken as the indicator of gastric cancer metastasis.